Areas of Outstanding Nineteenth Century Beauty: Historic landscape characterisation analysis of protected areas in England. Issue 1 (18th December 2022) - Stratigos, Michael J.; Ward, Caroline; Hatfield, Jack H.; Finch, Jonathan
Abstract: Establishing and expanding protected areas (PAs) has become a key conservation tool in efforts to halt global declines in biodiversity. Given the ubiquity of past and present human influence, PAs inevitably include landscapes and seascapes with varying levels of human modification. We briefly review the geographical biases in England's terrestrial PA network, noting that landscape‐scale PAs (National Parks and Areas of Outstanding Natural Beauty) across England disproportionately occupy rugged upland terrain of low agricultural value as a result of the specific history of PA creation, but that this also biases which historic landscapes compose PAs. We explore these biases using Historic Landscape Characterisation (HLC). Analysis of HLC revealed that PAs in our focal region in northern England are defined by land‐use changes and landscape reorganisation processes of the 18th and 19th centuries, primarily that of enclosure. The impact this landscape transformation had on biodiversity should now form a priority for further research. This historic landscape influence on PA designation has resulted in PAs being typically owned by large estates with consequences for their biodiversity, management and wider social impact (e.g. greater wealth inequalities). The results highlight that historic landscape perspectives are useful to address conservation priorities and practices related to the protection of biodiversity and could be especially helpful in understanding the interaction between biodiversity protection and historic land‐uses, ownership, management, access and other social impacts. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.